Endotracheal Tube Cuff Pressures in the Operating Room of a Pediatric Hospital: A Quality Improvement Initiative. Issue 6 (7th November 2022) - Moon, Kelly M.; Donaworth, Sherry; Hagele, Molly S.; Kim, Stephani S.; Willer, Brittany L.; Tobias, Joseph D.
Abstract : Introduction: Endotracheal tube (ETT) cuff pressures are frequently out of the recommended range of 20–30 cm H2 O. This can lead to multiple iatrogenic complications ranging from cough, sore throat, and tracheal edema to more serious medical issues such as tracheal stenosis, aspiration, nerve injuries, and tracheal rupture. Additionally, current methods to inflate ETT cuffs vary between anesthesia providers and are not consistent in the recommended range. The objective of this quality improvement project was to increase the percentage of cuff pressures between 20 and 30 cm H2 O. Methods: Four plan-do-study-act (PDSA) cycles were completed in the operating rooms at Nationwide Children's Hospital over 9 months to assess ways to improve the accuracy of obtaining recommended ETT cuff pressures. Control charts were used to evaluate the primary outcome measure. Results: Preimplementation, ETT cuff pressures were out of the recommended range 76% of the time. Cuff pressures were out of the recommended range 64% of the time with the addition of the air method, 84% of the time in the tidal volume ratio cycle, and 50% of the time using the removal of air technique. The removal of air method was the most effective in achieving cuff pressures within the recommended pressure range ( P < 0.001). Conclusions: Using quality improvement methodology, the percentage of ETT cuff pressures falling within the recommended pressure range increased using the removal of air technique. This approach is a simple and practical method that can be easily implemented in the clinical setting and would provide additional safety in the anesthetic management of pediatric patients.